Minimally invasive thorascopic surgery in treating congenital bronchobiliary fistula - Zengmeng Wang; Yajun Chen; Jinshi Huang; Chunhui Peng; Wenbo Pang; Dongyang Wu; Zhenhua Cao (Elsevier, 2020)
We summarized our minimally invasive thorascopic surgical experience of a rare congenital bronchobiliary fistula case and made a brief review of the literature. To our knowledge this is the first reported case treated by a total minimally invasive thorascopic surgery. Typical symptoms and signs, surgical experience, and pathological results were summarized with pictures. Intra-operative fistulography is of great importance to surgical decision making. Minimally invasive thorascopic surgery is safe and feasible in treating congenital bronchobiliary fistula without coexisting biliary tract malformation.